Implantación de contabilidad avicola en la granja del señor Luis Manfredo Gallardo Bravo, del cantón Balsas, provincia de el Oro periodo octubre a diciembre del 2013 - Suárez Armijos, Norma Bélgica (2014)
The thesis called IMPLEMENTATION OF ACCOUNTING POULTRY FARM BY MR LUIS GALLARDO MANFREDO BRAVO, THE CANTON BALSAS, PROVINCE OF GOLD PERIOD OCTOBER TO DECEMBER 2013, contributes significantly to their own way, because it allows you to know the costs incurred during the production of the poultry farm as well as the relevant procedures for efficient control of the resources available to achieve the optimization leads to improved business value. The application of the accounting process on the farm of Mr. Luis Bravo Manfredo Gallardo allowed to fulfill the objectives and where an initial inventory , plan and manual accounts only for agricultural activities performed , the accounting records and documents produced to facilitate the control of agricultural costs, supplies and materials , indirect labor and operating costs to thereby determine the unit and total cost of production and run the accounting process that may lead to obtain the financial statements during the period October to December 2013. Among the main conclusions after applying agricultural accounting in company subject to study , you get to determine the importance and necessity of the implementation of the accounting system according to their agricultural activities and needs for real data on its economic and financial situation and therefore take necessary corrective measures based on real data and objectives provides the financial statements. Key recommendations to help management undertaken by the owner, it is suggested that the supporting documents to control costs and are cost sheets , worksheets kardex and important documents in the process was applied.